Answer:
No, he is going to have $496, which is $4 dollars less than what he wanted.
Step-by-step explanation:
The first equation tells you that
. If you substitute this expression for
in the second, we have
![2x-(x+3)=-1 \iff x-3=-1 \iff x=2](https://tex.z-dn.net/?f=2x-%28x%2B3%29%3D-1%20%5Ciff%20x-3%3D-1%20%5Ciff%20x%3D2)
And we can deduce ![y=x+3=2+3=5](https://tex.z-dn.net/?f=y%3Dx%2B3%3D2%2B3%3D5)
Answer:
y≤x²+4x-1.
Step-by-step explanation:
1) to define the equation of the given graph; it is y=x²+4x-1 (its vertex is (-2;-5));
2) to define inequation accorging to the given graph (the area outside of the parabola means ≤).
X and x+1 are the numbers(x+1)+2x=223x+1=223x=22-13x=21x=21/3x=7 and x+1=8
Smaller number = 7
Larger number = 8